Copyright for the digital era: are we aiming at individuals? - Wiputhanupong, Chongnang (2016)
Individual persons are the most influential players in the online digital environment. Regarding their internet activities, these individual players could perform their role as either the original creator, the user, or the subsequent creator of the online digital works. When they are performing different roles, they are protected under different fundamental rights. For example, when online user borrows an online original works of the original creator to create online derivative works, two fundamental rights which are relevant are ‘copyright’ and ‘the right to freedom of expression’. The thesis focus on the rights of these online individual players in these two important aspects: copyright and the right to freedom of expression. Based on the inexplicable conflict between both rights, this thesis fundamentally argues that it is not as what was previously claimed that ‘copyright is the engine of free expression’. On the other hand, it is the other way around that ‘free expression is an engine of copyright’. This is following the logic of the deductive argument based on the evidence that ‘free expression is an engine of creative expression’ and ‘creative expression is an engine of copyright’. The argument above thus supports the importance of creativity in the copyright regime. It is thus certified that under the fundamental concept of copyright there lies a strong concept of system that protects and encourages the prosperity of human’s creativity under the term of authorship. Therefore, the protection of copyright in the digital era should not be directed away from this very fundamental concept. In terms of making online derivative works, this thesis therefore proposed that an exception of copyright infringement should be allowed for unauthorised user in so far as it encourages the prosperity of human’s creativity and does not conflict with a normal exploitation of the work and does not unreasonably prejudice the legitimate interests of the author, as certified under Article 9 of the Berne Convention. For this purpose, the thesis finally proposed that it is possible under the fundamental concept of copyright and the internet technology to create a distinction between the act of making adaptation and making publication of the online digital derivative works. This is, at least, to allow unauthorised making adaptation of the online digital works for prosperity of individual’s creativity, without re-publishing of those derivative works online.